Pemetaan Potensi Pengembangan Kopi di Kecamatan Sambas Berdasarkan Sifat Fisik Tanah dan Sistem Informasi Geografis - Masara'T, Sudirman; Sunardi, Sunardi; Sangkala, Sangkala (Department of Biology Education of Universitas Islam Negeri Alauddin Makassar, 2023)
The plantation sector is one of the area utilization activities that can significantly contribute to the income of rural communities, both in terms of providing employment and earning potential foreign exchange. These conditions are not supported by digitally integrated regional development information. This study aims to map the potential development of coffee plants in the Sambas sub-district based on the physical properties of the land presented in digital maps. The research was conducted in six villages within the Sambas sub-district administrative area using purposeful sampling. Within every village, three locations were chosen for soil sampling plots, each plot covering an area of 1 ha, and the sampling was done diagonally. The distance between each sampling plot is 5 km. Soil samples from each plot were then analyzed in the soil laboratory. The analysis results were processed using quantum GIS software to generate a digital map of land development potential. The results show a variety of land capability classes (classes II, III, and IV) with their respective limiting factors, namely drainage, flood threat, and soil texture. Land capability class II-d2 consists of locations A1, A2, A5, and A6. Land capability class III-d3O2 is at location A3, and capability class IV-t3.d4.O3 is at location A4.